2010
DOI: 10.1111/j.1095-8312.2010.01512.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and environmental influences on shape variation in the European sea bass (Dicentrarchus labrax)

Abstract: This paper demonstrates the contribution of both genetic and environmental effects on cultured European sea bass shape. We used the progeny of five populations of sea bass, in a partly diallel design, to investigate the genetics of shape (estimated with geometric morphometrics) in European sea bass. This was done using a common garden experiment with microsatellite markers assignment to parents and populations to avoid confusion between genetic and environmental effects. Additionally, one of the populations wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 45 publications
2
26
0
Order By: Relevance
“…Fish farms had on average lower K values than the wild populations. Over-all, among the Table 2 Description of the landmark points, adopted and modified from, (Costa et al 2010;Lorenz et al 2014;Ndiwa et al 2016;Peligro and Jumawan 2016) Landmark number Location description (Fig. 3a).…”
Section: Coefficient Condition (K)mentioning
confidence: 99%
See 1 more Smart Citation
“…Fish farms had on average lower K values than the wild populations. Over-all, among the Table 2 Description of the landmark points, adopted and modified from, (Costa et al 2010;Lorenz et al 2014;Ndiwa et al 2016;Peligro and Jumawan 2016) Landmark number Location description (Fig. 3a).…”
Section: Coefficient Condition (K)mentioning
confidence: 99%
“…GM is defined as the study of form in two or three dimensional spaces which induce in-depth investigation of morphological modelling in organisms (Bookstein 1982). GM allows the visualization and quantification of morphological differences in individuals represented by deformations of landmarks (Lms) in a coordinate space (Costa et al 2010;Park et al 2013). The arrangement of morphological Lms as data source and shape variation is extracted by Procrustes superimposition (Klingenberg 2011).…”
Section: Introductionmentioning
confidence: 99%
“…While some of these studies have found geographic concordance between morphologic and genetic data (Drew et al 2010) others have uncovered discordance between the measured morphological and genetic traits (Ho et al 2012). Similarly, several investigations on marine fishes have assessed the relationships between morphology and environmental factors; however, studies examining the relative contribution of environmental and genetic variation on morphology across natural populations are scarce (but see Marcil et al 2006;Costa et al 2010), and to our knowledge are lacking for coral reef fishes.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of severely deformed reared fish can cause consumers to lose confidence in aquaculture products [15] and reduce the commercial value of the reared lots [10][11], [13][14], [16][24]. Even automatic fillet processing is impaired by the presence of vertebral deformities, thus reducing economic return [25].…”
Section: Introductionmentioning
confidence: 99%